Determination of gestational age: correlation between foetal biometry and transverse cerebellar diameter in women with uncomplicated pregnancy - S. N., Pavithra; D., Vimala; G., Prema priya; R., Shankar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Transverse Cerebellar Diameter (TCD) serves as a reliable predictor of gestational age in foetus and is a standard against which aberrations in other foetal parameters can be compared, especially when the GA cannot be determined by the date of last menstrual period or early pregnancy scan, TCD is one foetal parameter that has remained consistently superior in predicting gestational age in both singleton and twin gestation. Aim of the study was to assess and evaluate the effectiveness of transverse cerebellar diameter by using ultrasonography for determining the gestational age of the foetus. Methods: A cross-sectional study was done in 100 uncomplicated pregnant patients between the 15th week of gestation to term referred from routine antenatal clinic in outpatient and in-patient department of Obstetrics and Gynecology department of Vinayaka Mission Krupananda Variyar medical college and hospital, Salem during study period April 2015-March 2016. TCD is obtained in the axial plane in the cerebellar view i.e. with a slight rotation of the transducer approximately 30° from the conventional thalamic plane where the biparietal diameter is measured using the cavum septi pellucidi, third ventricle and thalami as landmarks. Results: The correlation of transcerebellar diameter (TCD) with that of BPD (bi-parietal diameter) had shown a perfect positive correlation (r = 0.978) and a similar type of correlation was also seen with HC (head circumference) (r = 0.979), AC (abdominal circumference) (r = 0.966), FL (femur length) (r = 0.976) and USG GA (ultrasonogram gestational age) (r = 0.983). Conclusions: In the normally developing foetus, the TCD increases in a linear fashion with advancing gestational age. The data of this study suggest foetal TCD on ultrasound is a reliable predictive biometric parameter of gestational age.